BIOTEKNOLOGI DAN DILEMA RASIONALITAS TEKNOLOGI - Nurudin, Nurudin (Jurnal Bestari, 2001)
The development of biotechnology has had been between two rationalities both technological pole and ethical ones. Meanwhile technological rationality becomes an orientation of its development and human life both individual and social have be dehumanized. It is necessary that its development directs to the ethical rationality